2008
DOI: 10.1103/physrevb.77.092503
|View full text |Cite
|
Sign up to set email alerts
|

Self-energy renormalization around the flux phase in thetJmodel: Possible implications in underdoped cuprates

Abstract: The flux phase predicted by the t − J model in the large-N limit exhibits features that make it a candidate for describing the pseudogap regime of cuprates. However certain properties, as for instance the prediction of well defined quasiparticle peaks, speak against this scenario. We have addressed these issues by computing self-energy renormalizations in the vicinity to flux phase. The calculated spectral functions show features similar to those observed in experiments. At low doping, near the flux phase, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…This figure shows a crossover (double dashed dotted line) from a region of low intensity at low doping and high temperature to a region of high intensity at large doping and low temperature. 35 As in Ref. [76] we identify the former region with an incoherent metal where the QP peak is broad, whereas in the latter region the QP is well defined as expected for a coherent metal.…”
Section: -75mentioning
confidence: 94%
See 2 more Smart Citations
“…This figure shows a crossover (double dashed dotted line) from a region of low intensity at low doping and high temperature to a region of high intensity at large doping and low temperature. 35 As in Ref. [76] we identify the former region with an incoherent metal where the QP peak is broad, whereas in the latter region the QP is well defined as expected for a coherent metal.…”
Section: -75mentioning
confidence: 94%
“…32 These self-energy effects were recently confronted with experiments in the normal state, such as angle-dependent magnetoresistance (ADMR) 33 and ARPES, [34][35][36][37][38] after which they show qualitative agreement. We have shown that several aspects related to the Fermi arc phenomenology and ADMR features can be described considering self-energy effects near the FP instability.…”
Section: 30mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as discussed in Ref. 9 and summarized below, the relevant contributions to ⌺͑k , ͒ can be written as Im ⌺͑k,͒ = Im ⌺ R ͑k,͒ + Im ⌺ flux ͑k,͒ ͑5͒…”
Section: Summary Of the Formalism: Inelastic Scattering Ratementioning
confidence: 99%
“…[7] and [8] can be discussed in the framework of Refs. [11], [12], and [13] showing that a theory where the PG phase is distinct from SC and associated with short-range fluctuations in the proximity to a symmetry breaking instability is consistent with the experiment.…”
Section: Andrés Greco and Matías Bejasmentioning
confidence: 58%